Combination of AAV-delivered tumor suppressor PTEN with anti-PD-1 loaded depot gel for enhanced antitumor immunity - Yongshun Zhang; Lan Yang; Yangsen Ou; Rui Hu; Guangsheng Du; Shuang Luo; Fuhua Wu; Hairui Wang; Zhiqiang Xie; Yu Zhang; Chunting He; Cheng Ma; et al. (Elsevier, 2024)
Recent clinical studies have shown that mutation of phosphatase and tensin homolog deleted on chromosome 10 (PTEN) gene in cancer cells may be associated with immunosuppressive tumor microenvironment (TME) and poor response to immune checkpoint blockade (ICB) therapy. Therefore, efficiently restoring PTEN gene expression in cancer cells is critical to improving the responding rate to ICB therapy. Here, we screened an adeno-associated virus (AAV) capsid for efficient PTEN gene delivery into B16F10 tumor cells. We demonstrated that intratumorally injected AAV6-PTEN successfully restored the tumor cell PTEN gene expression and effectively inhibited tumor progression by inducing tumor cell immunogenic cell death (ICD) and increasing immune cell infiltration. Moreover, we developed an anti-PD-1 loaded phospholipid-based phase separation gel (PPSG), which formed an in situ depot and sustainably release anti-PD-1 drugs within 42 days in vivo. In order to effectively inhibit the recurrence of melanoma, we further applied a triple therapy based on AAV6-PTEN, PPSG@anti-PD-1 and CpG, and showed that this triple therapy strategy enhanced the synergistic antitumor immune effect and also induced robust immune memory, which completely rejected tumor recurrence. We anticipate that this triple therapy could be used as a new tumor combination therapy with stronger immune activation capacity and tumor inhibition efficacy.